Time dependence of reliability of noncontrast computed tomography in comparison to computed tomography angiography source image in acute ischemic stroke. Issue 1 (13th September 2012) - Bal, Simerpreet; Bhatia, Rohit; Menon, Bijoy K.; Shobha, Nandavar; Puetz, Volker; Dzialowski, Imanuel; Modi, Jayesh; Goyal, Mayank; Hill, Michael D.; Smith, Eric E.; Demchuk, Andrew M.
<x xml:space="preserve">Abstract</x> There is no consensus on how the reliability and predictive ability of noncontrast computed tomography (NCCT) and computed tomography angiography source image (CTASI) change over time from acute ischemic stroke onset. We hypothesized that the reliability for detecting early ischemic changes (EIC) would be lower in early time periods and that changes identified on CTASI would be more reliable across examiners than changes identified on NCCT. To address this, we compared the relationships between CTASI, NCCT, and final infarct in patients with initial computed tomography (CT) imaging at different time points after stroke onset. Patients with acute ischemic stroke with proximal anterior circulation occlusions (internal carotid artery, middle carotid artery M1, proximal M2) from Calgary CT Angiography (CTA) database were studied. The cohort was categorized in four groups based on time from stroke onset to baseline NCCT/CTA: 0–90 mins (n = 69), 91–180 mins (n = 88), 181–360 mins (n = 46), and >360 mins (n = 58). Median scores of NCCT‐Alberta Stroke Program Early CT Score (ASPECTS), CTASI ASPECTS, and follow‐up ASPECTS among different time categories were compared. To determine reliability, a subsample of NCCT brain and CTASI were interpreted at separate sessions weeks apart by two neuroradiologists and two stroke neurologists in random order. Median and mean ASPECTS ratings on NCCT and CTASI were higher than final ASPECTS in each time category (P < 0·001 for all comparisons). CTASI ASPECTS was lower than NCCT ASPECTS in each time category, and differences were significant at 0–90 mins and 91–180 mins (P < 0·001). The least agreement among readers was in detection of EIC on NCCT brain in the ultra‐early phase (<90 mins) [intraclass correlation coefficient (ICC) = 0·48. By contrast, there was excellent agreement on EIC on CTASI regardless of time period (ICC = 0·87–0·96). Using ASPECTS methodology, CTASI is more reliable than NCCT at predicting final infarct extent particularly in the early time windows.